OVERWEIGHT AND OBESITY IN ADOLESCENTS: THE INFLUENCE OF PHYSICAL ACTIVITY LEVEL (Fiep Bulletin - online, 2013)
The current study aimed to determine the prevalence of obesity and overweight in adolescents in the city of Imperatriz, Maranhão, Brazil, and to identify the influence of IMC on the NAF. The research involved a sample of 118 students aged between 14 and 18 years, enrolled in high school and frequently, from a public university, chosen by availability. Students were selected by simple random sampling method and underwent two evaluations: anthropometry (weight, height and IMC) and questionnaire. The results of the analysis of LPA and its relationship with IMC and gender was observed that the majority of children (82.9%) were classified as normal weight and physically active (66.1%) according to elevated IMC occurs a reversal in activity level, a slope of overweight adolescents toward sedentary lifestyle, this group evaluated. It was concluded in this study that the prevalence of overweight and obesity in adolescents assessed is present mainly in males, but these present themselves more physically active than their female peers.
Keywords: adolescence; BMI; obesity